Imperfect substitutes: competitive analysis failure in US intercity passenger rail. (20th October 2006) - Rhoades, Dawna L.; Williams, Michael J.; Green, Dustin J.
The National Railroad Passenger Corporation (Amtrak) has come under increasing scrutiny from a US Administration whose 2006 budget called for no operating subsidies for the company which continues to lose money on all but a few of its routes. Supporters argued that after September 11th, ridership would increase as US consumers sought alternative means of transportation. This study reports on research conducted in the first quarter of 2005 comparing US air carriers with Amtrak service. The conclusion is that efforts by Amtrak to compete with air carriers on most of their routes are likely to be ineffective and costly.